(untitled) (Comparatismi, 2022)
Shortly after the Second World War and the atomic bombings of Hiroshima and Nagasaki, author Numa Shōzō serialised the novel Kachikujin Yapoo (Yapoo the Human Cattle, 1956) in the magazine «Kitan Club» (Club of Bizarre Tales). Through a sci-fi setting and radical masochistic imagery, Numa stages an ultra-racist dystopia dominated by Aryan women in which Japanese survivors of a Third World War are degraded to subhuman creatures and genetically manipulated. The novel articulates with a Swiftian plot a dialogue with the oldest sources of Japanese myths to deconstruct the sacredness on which the Japanese imperialist dream was founded. This paper aims to analyse these themes to identify the relationship between the re-enactment of trauma and Numa’s masochistic and sci-fi literary imagery.